Playful Learning: Developing Daily Life Skills in Early Childhood (Current Research in Education: Conference Series Journal, 2024)
The purpose of this study was to find out that playing while learning can develop children's daily life skills. The research method used is a systematic literature review. Based on the results of research conducted, Playful-learning is a learning method that is appropriate to the characteristics of children and is able to develop children's life skills through fun activities so that learning will feel more meaningful. Playing together is a world that cannot be separated from early childhood life. So that learning activities often adopt learning methods that are closely related to playing methods. However, it is often found that learning and playing activities are two separate things. It seems as if children cannot develop aspects of their development through play activities alone. Therefore, to create a suitable learning environment for children, it is necessary to integrate the two through the Playful-Learning method. Learning for children is not only enough from an academic point of view, but also must pay attention to aspects of life skills to make it easier for them to live in the future.